Educational Robotics as a motivating methodology in the teaching of programming logic in Professional and Technological Education (Research, Society and Development, 2020)
This article aims to detail the use of the educational product called Robôcactus as a theoretical-methodological tool, associated with educational robotics and the Arduino platform in Professional and Technological Education (EPT). Therefore, this work uses the methodology of participatory action research, the active methodologies of Inverted Classroom (SAI) and Project Based Learning (PBL). Besides of the difficulties and demotivation of students in the programming logic component, a methodology was created to mitigate this impact by conducting an educational robotics workshop that aims to contribute beyond the subject's polytechnic education, but also his critical thinking and technical knowledge through of praxis, where such factors are very important for the development of the 21st century professional. The content analysis reveals the positive experience of using robotics as a technological motivating agent in the school environment.